2022
DOI: 10.1002/lsm.23611
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and characterization of facial skin aging using optical coherence tomography

Abstract: Objectives: The skin aging exposome encompasses internal and external factors that contribute to clinical signs of facial aging. Aging skin can be characterized by distinctive features such as wrinkles, lentigines, elastosis, and roughness. Optical coherence tomography (OCT) is capable of noninvasively measuring skin characteristics. This study aimed to assess bilateral features using OCT to explore temporal skin changes among decades and potential changes in facial skin aging based on laterality. Methods: A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…In addition, changes in the aging dermis include decreased vascularity [ 19 ] and density of collagen fibers [ 16 , 20 ]. These changes can also reduce the dermal scattering coefficient, as was demonstrated recently using optical coherence tomography (OCT) [ 21 ].…”
Section: Introductionmentioning
confidence: 87%
“…In addition, changes in the aging dermis include decreased vascularity [ 19 ] and density of collagen fibers [ 16 , 20 ]. These changes can also reduce the dermal scattering coefficient, as was demonstrated recently using optical coherence tomography (OCT) [ 21 ].…”
Section: Introductionmentioning
confidence: 87%
“…17 Hence, it is the most appropriate imaging tool for long-term in vitro and in vivo skin studies, particularly for monitoring morphological changes in anti-aging analyses. [18][19][20] Notably, the 3D volumetric image generated by OCT showed robust and accurate measurements in a repeated experiment. Furthermore, since skin aging progresses simultaneously in epidermis and dermis, OCT-assisted monitoring and analyses of the inner structure of the skin surface would be beneficial.…”
mentioning
confidence: 90%
“…Moreover, this is a non‐invasive process involving no contrast agent and labeling step 17 . Hence, it is the most appropriate imaging tool for long‐term in vitro and in vivo skin studies, particularly for monitoring morphological changes in anti‐aging analyses 18–20 . Notably, the 3D volumetric image generated by OCT showed robust and accurate measurements in a repeated experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The results from an observational study included a significantly decreased dermal attenuation coefficient and trends of increased roughness with age. 19 The authors concluded that the technology has the potential to personalize therapies based on objective findings. Indeed, in a recent systematic review and meta‐analysis OCT was shown to improve the detection of persistent basal cell carcinoma (BCC) after medical treatment.…”
Section: Introductionmentioning
confidence: 99%